Use of supplementary cementitious materials (SCMs) in reinforced concrete systems – Benefits and limitations - Pillai, Radhakrishna G.; Gettu , Ravindra; Santhanam, Manu (Revista ALCONPAT, 2020)
About a decade of research carried out at IIT Madras on cementitious systems has shown that the partial replacement of portland cement with supplementary cementitious materials (SCMs) has benefits as well as limitations. The SCMs do not adversely affect the long-term compressive strength and drying shrinkage of concretes, though there may be some compromise in workability and the resistance against plastic shrinkage cracking. Through the assessment of the chloride ingress rate in concrete and chloride threshold of steel, it is evident that the use of SCMs could significantly enhance the service life under chloride attack, though there is a reduction of the carbonation resistance. More importantly, SCMs can lead to significant reduction of the carbon footprint of concrete, and hence, are essential to achieve sustainability.